2004
DOI: 10.1158/1078-0432.ccr-03-0541
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase IX as a Marker for Poor Prognosis in Soft Tissue Sarcoma

Abstract: Purpose: Hypoxia is associated with malignant progression and poor outcome in several human tumors, including soft tissue sarcoma. Recent studies have suggested that carbonic anhydrase (CA) IX is an intrinsic marker of hypoxia, and that CA IX correlates with poor prognosis in several types of carcinoma. The aim of this study was to quantify the extent of CA IX expression and to investigate whether CA IX is a marker for poor prognosis in soft tissue sarcoma patients at high risk of developing metastasis.Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 28 publications
0
61
0
1
Order By: Relevance
“…There are numerous reports showing that CA IX acts not only as a marker for particular tumors, but its presence also correlates to prognosis in several tumor categories, such as brain tumors, sarcomas, and renal, lung, rectal, bladder, oral, breast, and cervical carcinomas [7,[27][28][29][30][31][32][33][34]. Although studies on CA II and CA XII have been mainly focused on normal tissues, there are a few previous reports, showing their presence in cancer cells and especially in brain tumors where they have shown significant association with prognosis [6,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports showing that CA IX acts not only as a marker for particular tumors, but its presence also correlates to prognosis in several tumor categories, such as brain tumors, sarcomas, and renal, lung, rectal, bladder, oral, breast, and cervical carcinomas [7,[27][28][29][30][31][32][33][34]. Although studies on CA II and CA XII have been mainly focused on normal tissues, there are a few previous reports, showing their presence in cancer cells and especially in brain tumors where they have shown significant association with prognosis [6,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…this is a cancer-associated antigen recognized by antibodies, produced by cervical cancer or renal cell carcinoma cells, and is expressed in normal tissues of gastrointestinal tract membranes, bile ducts (7) and skin (unpublished data). recently, many research groups have reported its expression not only in renal cell carcinoma and cervical cancer, but also in bladder cancer, non-small cell lung cancer, breast cancer, head and neck cancer, esophageal cancer, stomach cancer, large intestine cancer, bile duct cancer, sarcoma and chronic myeloid leukemia (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). yoshikawa et al prepared mousederived renal cell carcinoma cells expressing human cA9 antigen.…”
Section: Introductionmentioning
confidence: 99%
“…32 CA-9 is a well-known marker of tumor hypoxia identifiable by its intense surface membrane staining, commonly seen in hypoxic tissue. [33][34][35] Recently, Iakovlev et al 36 showed that CA-9 labeling was correlated with direct pO 2 measurements in cervical carcinoma and that there was significant intratumoral heterogeneity. Our study further supports CA-9 as a suitable marker for identifying hypoxia and presents findings showing upregulated expression of a series of metastasis-related genes in sorted CA-9-positive (hypoxic) cells.…”
mentioning
confidence: 99%